If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65t + 7 = 83 Reorder the terms: 7 + 65t = 83 Solving 7 + 65t = 83 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 65t = 83 + -7 Combine like terms: 7 + -7 = 0 0 + 65t = 83 + -7 65t = 83 + -7 Combine like terms: 83 + -7 = 76 65t = 76 Divide each side by '65'. t = 1.169230769 Simplifying t = 1.169230769
| b-10=-7 | | 13x+2=8-2x | | 3x=.87 | | (x+3)(x+k)(x-5)=-3 | | -8=n+(-18) | | 3x=-2x-3-1 | | 4x^2+10x=-7x | | -3x^3+x^2+75x-25=0 | | 2x-(6-x)=3x-6 | | 8x^6-2=0 | | 36X^2y^2+84xy+49=0 | | 52d+4=88d+2 | | 12700x=94.5x+2*x^2 | | 11+m=30 | | 36X^2+84xy+49=0 | | 3(2t+1)-2(t-2)=5 | | 88+2d=52+4d | | b-10=-17 | | z^2+6z+7=0 | | 4x^2+4xy=0 | | 2(v-1)+4v=3(2v-1)+8 | | p+10=3 | | 0.09+0.14(10000-x)=1275 | | 2+2=45x | | 5x-11=4x-14 | | 3x-7=6+4x | | 2r+5+2r+4r-3+r=65 | | lx-4l=-15 | | t=4s+4.95 | | -5-4=9 | | -8=-(7n+1) | | (5x+3)(6x-8)= |